Komunikasi, Informasi, dan Edukasi Pterigium pada Nelayan di Desa Laha, Kecamatan Teluk Ambon, Ambon Tahun 2023 - Abdillah A. F. Hasanusi; Nathalie E. Kailola (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Coastal communities represent a population at high risk of developing diseases associated with excessive ultraviolet (UV) exposure, such as pterygium. Pterygium is one of the most common ocular surface disorders. This community service program aimed to provide Communication, Information, and Education (CIE) regarding pterygium to fishermen in Laha Village, Teluk Ambon District, Ambon, in 2023. The activity was carried out on September 24, 2023, in Laha Village, Teluk Ambon District, Ambon City, and involved 24 participants, the majority of whom were fishermen. The program consisted of two main components: health education on pterygium and distribution of informational leaflets. The implementation of the CIE program on pterygium in Laha Village effectively increased fishermen’s knowledge and awareness of pterygium risk factors as well as the importance of early prevention. This achievement was supported by a combination of instructional methods, interactive discussions, and the provision of educational leaflets that successfully conveyed essential health information